The informative contribution of photography in Spanish digital native journalistic media. Updated analysis of relevant factors and basic iconic-textual relationships - López del Ramo, Joaquín; Humanes Humanes, María Luisa (Revista General de Información y Documentación, 2024)
The exponential growth of digital native newspapers and their audiences stimulates interest in the informative content of these media as an object of research in Communication. Among the least studied news components are photography and semantic relationships with the headlines they accompany. This article empirically examines both factors. Base on a content analysis, a coding sheet of its own design is applied to a sample of 602 units from four Spanish press releases in this area. The essential objective is to determine the informative contribution of photography in conventional news, analyzing its contents and its degree of semantic agreement with the headline, in relation to the sections where they are published. The conclusions indicate that the images show few details, they are simple and obvious, and their significant link with the headline of the news, without being dissonant, is not very direct or clear either. Thus, the informative contribution is generally superficial, it only reflects the most obvious, and also easier to record aspects, and those that require less effort. These trends are more accentuated in the Economics section. It is worth considering as an influencing factor that today access to news is carried out mainly through mobile devices and in open contexts, which promotes superficial and fast reading habits.